Partisipasi Masyarakat dalam Menyelenggarakan Program Kelompok Bermain (KB) Permata Bunda di Desa Pucangrejo Kecamatan Sawahan Kabupaten Madiun - Ananda Ida Budiasa; Widya Nusantara (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This study aims to determine the process and form of community participation in the implementation of the Permata Bunda Play Group (KB) program. This study uses a research method with a descriptive qualitative approach. The subjects of this study were KB Permata Bunda educators, guardians of KB Permata Bunda students, PKK Cadres in Pucangrejo Village, and the Head of Pucangrejo Village. Data collection was carried out in 3 ways, namely participatory observation, in-depth interviews, and documentation. Data analysis techniques are data condensation, data display, and drawing conclusions. The results of this study indicate that there is participation provided by the community, namely educators, parents of students, PKK cadres, and village heads. Participation provided by the community can be formed because of the attitude of mutual cooperation and cooperation that is embedded in the community. This participation is manifested in various activities in the implementation of the Permata Bunda KB, namely teaching and learning activities (KBM), Activities for Implementing Clean and Healthy Living (PHBS), as well as non-academic activities such as outbound and commemoration of holidays. The types of participation provided by various levels of society are adjusted to the capacity and needs in organizing the KB Permata Bunda.